THE IMPACT OF SOCIO-EMOTIONAL INTELLIGENCE ON ACADEMIC PERFORMANCE - Turi, Jamshid Ali; Ghani, Muhammad Faizal A.; Javid, Yasir; Sorooshian, Shaharyar (Universitas Pendidikan Indonesia, 2018)
The study was designed to check the impact of socio-emotional intelligence on academic performance of the university students. The target population was BS, MS and PhD students of the COMSATS institute for information technology. Self-administered questionnaire based survey method was adopted using Bar On EQ-I questionnaire for data collection based on non-random sampling (Convenient) sampling method. Results indicate positive correlation between socio-emotional intelligence and academic performance and the results recommend penetration of socio-emotional intelligence practices in teaching learning processes for getting best possible academics objectives.